Understanding variation in unplanned admissions of people aged 85 and over: a systems-based approach. Issue 7 (9th July 2019) - Wilson, Andrew; Baker, Richard; Bankart, John; Banerjee, Jay; Bhamra, Ran; Conroy, Simon; Kurtev, Stoyan; Phelps, Kay; Regen, Emma; Rogers, Stephen; Waring, Justin
Abstract : Aim: To examine system characteristics associated with variations in unplanned admission rates in those aged 85+. Design: Mixed methods. Setting: Primary care trusts in England were ranked according to changes in admission rates for people aged 85+ between 2007 and 2009, and study sites selected from each end of the distribution: three 'improving' sites where rates had declined by more than 4% and three 'deteriorating' sites where rates had increased by more than 20%. Each site comprised an acute hospital trust, its linked primary care trust/clinical commissioning group, the provider of community health services and adult social care. Participants: A total of 142 representatives from these organisations were interviewed to understand how policies had been developed and implemented. McKinsey's 7S framework was used as a structure for investigation and analysis. Results: In general, improving sites provided more evidence of comprehensive system focused strategies backed by strong leadership, enabling the development and implementation of policies and procedures to avoid unnecessary admissions of older people. In these sites, primary and intermediate care services appeared more comprehensive and better integrated with other parts of the system, and policies in emergency departments were more focused on providing alternatives to admission. Conclusions: Health and social care communities which have attenuated admissions of people aged 85+ prioritised developing a shared vision and strategy, with sustained implementation of a suite of interventions.